IT and Curriculum Processes: Dilemmas and Challenges - Voogt, Joke (International Handbook of Information Technology in Primary and Secondary Education, 2008)
According to policy makers, education has to change to prepare students for the information or knowledge society. IT plays an important role in realizing such change. However, evidence shows that the intentions of policy makers do not always match with the use of IT in educational practice. In addition students’ attainments in an IT-supported curriculum often do not reflect the expectations of IT for teaching and learning. This chapter discusses the dilemmas and challenges of IT integration in the curriculum. For the integration of IT the main task is to bridge the gap between intentions (the intended curriculum), realization (the implemented curriculum) and outcomes (the attained curriculum).
Keywords: TICE; numérique